The oil industry in a burning world: how can unitilization shape the oil industry to mitigate climate change? - López Rangel, Fernando; Vieira da Fonseca Rocha, Raphael (Homa Publica - Revista Internacional de Derechos Humanos y Empresas, 2024)
Countries and companies likewise ought to take ever more bolder actions due to the aggravation of climate change impacts. Taking this into consideration, the international community and its actors have been seeking commitments to renew climate actions and fulfill the transition to a sustainable society. The need to take actions to mitigate and to adapt to climate change impacts, and hence promoting justice, encompasses all human activities. As such, energy production takes a special place in the green transition. It massively contributes to human-driven climate change through high GHG emissions. Nevertheless, it still lacks international binding rules, comprehensive governance and innovative policies. Indeed, before full-fledge transition, international climate bodies recognize the urgency of short-term solutions. Thus, practices that enhance energy efficiency become much needed climate actions. Unititzation presents itself as a widespread practice in national jurisdictions. However, it is not properly implemented in many countries and does not encompass international oil fields. Considering the commitments undertaken, the costumes and rules in regard to climate, one must reach the conclusion that unitization has become mandatory practice in oil extraction, production and transportation in order to reduce waste and improve energy efficiency. States’ duties do not end in cooperation, common procedures and rules must accompany the development of joint oil and gas reserves.